Emotion Focused Coping pada Penggemar K-Pop yang Fanatik - Asri Rejeki; Awang Setiawan Wicaksono; Nur Riza Amalia (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine Emotion Focused Coping in fanatic K-pop fans. The approach used in this research is qualitative research with a case study type. The subjects in this study amounted to 3 K-pop fans entering early adulthood. Data collection techniques using interview methods, data analysis techniques using Miles and Huberman. The data reliability techniques used are method triangulation and source triangulation. The results of this study indicate that they have fanatical behavior, the three subjects both said that K-pop has a big influence on them because K-pop is a comfortable place for the subject if the subject often feels stressed or tired in real life or from work or others, K-pop can make the subject happy again through songs and others.